2022
DOI: 10.1038/s41598-022-18572-3
|View full text |Cite
|
Sign up to set email alerts
|

Local anesthetic lidocaine-inducible gene, growth differentiation factor-15 suppresses the growth of cancer cell lines

Abstract: Administration of local anesthetics, such as lidocaine, in the perioperative period improves outcomes of cancer patients. However, its precise mechanism is still unresolved. The growth of human cancer cell lines, including HeLa cells, are suppressed by lidocaine treatment. We identified that growth differentiation factor-15 (GDF-15) was commonly upregulated in lidocaine-treated cancer cell lines. GDF-15 is a divergent member of the transforming growth factor-β (TGF-β) superfamily and it is produced as an unpro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…It has been proposed that catecholamines, released during acute myocardial or cerebral ischemia, may remotely induce GDF15 secretion 18 . In a recent study, local anaesthetics such as lidocaine were shown to upregulate GDF15 production in HeLa cultured cells 19 , suggesting lidocaine use in our surgical procedure could contribute to the GDF15 secretion observed in both I/R and Sham rats. Additionally, two studies indicate that coronary artery bypass grafting in patients increases GDF15 plasma level by 2.5-or 3-fold compared to anaesthesia induction level 20,21 .…”
Section: Discussionmentioning
confidence: 78%
“…It has been proposed that catecholamines, released during acute myocardial or cerebral ischemia, may remotely induce GDF15 secretion 18 . In a recent study, local anaesthetics such as lidocaine were shown to upregulate GDF15 production in HeLa cultured cells 19 , suggesting lidocaine use in our surgical procedure could contribute to the GDF15 secretion observed in both I/R and Sham rats. Additionally, two studies indicate that coronary artery bypass grafting in patients increases GDF15 plasma level by 2.5-or 3-fold compared to anaesthesia induction level 20,21 .…”
Section: Discussionmentioning
confidence: 78%
“…It has been proposed that catecholamines, released during acute myocardial or cerebral ischemia, may remotely induce GDF15 secretion 28 . In a recent study, local anaesthetics such as lidocaine were shown to upregulate GDF15 production in HeLa cultured cells 38 , suggesting that lidocaine use in our surgical procedure may have contributed to the GDF15 secretion observed in both I/R and sham rats. Additionally, two studies indicate that coronary artery bypass grafting in patients increases GDF15 plasma level by 2.5- or 3-fold compared to anaesthesia induction level 39 , 40 .…”
Section: Discussionmentioning
confidence: 82%
“…Importantly, MKI67 gene encoding Ki-67 is the target for E2F (Sun & Kaufman, 2018). Our RNA sequencing analysis (RNA-seq) using human cancer cell lines involving HeLa cells revealed that Ki-67 was commonly downregulated by lidocaine treatment (sequence data are available from ArrayExpress under the accession number E-MTAB-11320, https://www.ebi.ac.uk/ arrayexpress/experiments/E-MTAB-11320/), suggesting that lidocaine might function as an antitumor drug through regulating Ki-67 expression at transcriptional level in addition to posttranslational levels such as via the proteasome pathway (Haraguchi-Suzuki et al, 2022).…”
Section: Discussionmentioning
confidence: 99%